Transurânicos em reator a gás de alta temperatura - Angela Fortini Macedo Ferreira (2014)
In this work, we modeled a high temperature gas reactor, HTGR, of prismatic block type using the SCALE 6.0 code to analyze the use of transuranic fuel in these reactors. To represent the concept, the Japanese HTTR reactor was chosen. The fuels considered used transuranic elements from UREX+ reprocessing of burned PWR fuel spiked with depleted U or Th. The calculations, performed for typical temperatures of HTR reactors, showed that, in mixtures with the same percentage of fissile material, the initial effective multiplication factor, keff , is higher in the mixtures containing Th than that with U. Comparisons between the two types of fuel were performed using fuel pairs with the same initial keff. During burn-up, the two mixtures result in a slow and practically equal decrease in keff. For the same level of burnup, mixtures containing Th show greater effectiveness in burning transuranics and total plutonium when compared to corresponding mixtures with depleted U. The calculation of temperature reactivity coefficient proved appropriate behavior in terms of safety of the reactor working with these fuels. The radiotoxicity of spent fuels immediately after the burning increases with increasing burnup. However, due to faster decay of fissionable products at high burnup levels, radiotoxicity after 1000 years diminishes with increasing burnup. Actinides become responsible for most of the radiotoxicity in less than 10 years after burn. It is also lower in mixtures with Thorium than in mixtures Uranium.